Monetary Policy in the Aftermath of Currency Crises : The Case of Asia - Baig, Taimur; Goldfajn, Ilan. (Washington, D.C. : International Monetary Fund, 1998)
This paper evaluates monetary policy and its relationship with the exchange rate in five Asian crisis countries. The findings are compared with previous currency crises in recent history. The paper finds no evidence of overly tight monetary policy in the Asian crisis countries in 1997 and early 1998, nor evidence that high interest rates led to weaker exchange rates. The usual trade-off between inflation and output when raising interest rates suggested the need for a softer monetary policy in the crisis countries to combat recession. However, in some countries, corporate balance sheet considerations called for the reversal of overly depreciated currencies through firmer monetary policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet